2020
DOI: 10.1021/acsabm.0c00159
|View full text |Cite
|
Sign up to set email alerts
|

Silver–Polymethylhydrosiloxane Nanocomposite Coating on Anodized Aluminum with Superhydrophobic and Antibacterial Properties

Abstract: Biofilm formation on both animate and inanimate surfaces serves as an ideal bacterial reservoir for the spread of nosocomial infections. Designing surfaces with both superhydrophobic and antibacterial properties can help reduce initial bacterial attachment and subsequent biofilm formation. In the present study, a two-step approach is deployed to fabricate silver–polymethylhydrosiloxane (Ag–PMHS) nanocomposites, followed by a simple dip-coating deposition on anodized Al. Ag-nanoparticles (Ag-NPs) are synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 63 publications
2
25
0
Order By: Relevance
“…Alternatively, to fabricate coatings that are fouling-resistant and bactericidal via release-kill, surface-grafted zwitterionic/nonionic/anionic hydrophilic polymer can be loaded with bactericidal release agents. Bactericidal agents can also be loaded in polymeric coatings with fouling-release properties (Figure A). Examples include hydrophobic fluorinated polymers loaded with bactericidal agents like povidone-iodine or silver (Ag) NPs, silicone-based elastomer loaded with Ag NPs, and a superhydrophobic polymeric layer loaded with Ag NPs . On the other hand, fouling-release polymers are generally not combined with contact-active polymers because bacteria adhere strongly to the latter via electrostatic interactions and are thus difficult to be “released” by the application of shear force.…”
Section: General Antifouling and Bactericidal Strategiesmentioning
confidence: 99%
“…Alternatively, to fabricate coatings that are fouling-resistant and bactericidal via release-kill, surface-grafted zwitterionic/nonionic/anionic hydrophilic polymer can be loaded with bactericidal release agents. Bactericidal agents can also be loaded in polymeric coatings with fouling-release properties (Figure A). Examples include hydrophobic fluorinated polymers loaded with bactericidal agents like povidone-iodine or silver (Ag) NPs, silicone-based elastomer loaded with Ag NPs, and a superhydrophobic polymeric layer loaded with Ag NPs . On the other hand, fouling-release polymers are generally not combined with contact-active polymers because bacteria adhere strongly to the latter via electrostatic interactions and are thus difficult to be “released” by the application of shear force.…”
Section: General Antifouling and Bactericidal Strategiesmentioning
confidence: 99%
“…They demonstrated that such antibacterial superhydrophobic coatings could be used to design marine coatings to efficiently prevent or reduce bacterial microorganism adhesion. Agbe et al [ 65 ] fabricated an silver‐polymethylhydrosiloxane (Ag‐PMHS) superhydrophobic nanocomposite coatings, which demonstrated excellent antibacterial properties against clinically relevant planktonic bacteria with zone of influence (ZOI) values of 25.3 ± 0.5, 24.8 ± 0.5, and 23.3 ± 3.6 mm for Pseudomonas aeruginosa ( P. aeruginosa ), Escherichia coli ( E. coli ), and Staphylococcus aureus ( S. aureus ), respectively ( Figure ). And the as‐synthesized coatings also provided excellent antibiofouling properties with bacterial adhesion reductions of 99.0%, 99.5%, and 99.3% for P. aeruginosa , E. coli , and S. aureus , respectively.…”
Section: Metal‐based Antibacterial Superhydrophobic Coatingsmentioning
confidence: 99%
“…Reproduced with permission. [65] Copyright 2020, American Chemical Society. Reproduced with permission.…”
Section: Zno-contained Antibacterial Superhydrophobic Coatingsmentioning
confidence: 99%
“…Now, we know that the length of existence time of the air-bubble layer directly affects the antibiofouling property of the surface. Also, the air-bubble layer is mainly determined by material chemical composition and surface morphological structure of the coating. , Compared with superhydrophobic coating, fluorinated carbon nanotubes superamphiphobic coating with super oil repellency, lower surface free energy, and stable re-entrant micro/nanostructures will be a great choice because lower surface free energy and stable re-entrant micro/nanostructures can promote the appearance of a better air-bubble layer with fewer defects and further guarantee the chronic existence of the air-bubble layer on the surface. Meanwhile, the existence of long fluorinated chains, which have been proven to reduce the affinity of the surface to proteins and bacteria, , will have a stronger and more durable adverse impact on protein adsorption and bacterial attachment.…”
Section: Introductionmentioning
confidence: 99%